2019
DOI: 10.1136/bmjopen-2019-031327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a mindful-eating programme to reduce emotional eating in patients suffering from overweight or obesity in primary care settings: a cluster-randomised trial protocol

Abstract: IntroductionLittle is known about the applicability of mindfulness-based interventions in Spanish adults with overweight/obesity. The objective of the present study protocol is to describe the methods that will be used in a cluster randomised trial (CRT) that aims to evaluate the effectiveness of a mindfulness eating (ME) programme to reduce emotional eating (EE) in adults with overweight/obesity in primary care (PC) settings.Methods and analysisA CRT will be conducted with approximately 76 adults with overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 145 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…An 8-week behavioral intervention program with a focus on mindful eating among overweight and obese premenopausal women showed an improvement in the awareness of hunger cues, decreased reliance on external cues for eating, and increased food enjoyment [ 27 ]. Moreover, a 6-week primary care mindful eating program found significant improvements in emotional eating, mindful eating, and a decrease in eating in response to external cues [ 28 ]. Our study findings suggest that teaching kitchens can similarly be effective in improving eating behaviors, including mindful eating.…”
Section: Discussionmentioning
confidence: 99%
“…An 8-week behavioral intervention program with a focus on mindful eating among overweight and obese premenopausal women showed an improvement in the awareness of hunger cues, decreased reliance on external cues for eating, and increased food enjoyment [ 27 ]. Moreover, a 6-week primary care mindful eating program found significant improvements in emotional eating, mindful eating, and a decrease in eating in response to external cues [ 28 ]. Our study findings suggest that teaching kitchens can similarly be effective in improving eating behaviors, including mindful eating.…”
Section: Discussionmentioning
confidence: 99%
“…The confidentiality of participants was guaranteed and protected by the Spanish Organic Law on Protection of Personal Data and Guarantee of Digital Rights (3/2018 of December 7), and all relevant EU legislation on privacy and data protection. This trial ( ClinicalTrials.gov NCT03927534) was performed in compliance with the study protocol, where more details of the procedures can be found (Morillo‐Sarto et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the TAU included two interviews with the GP and a nurse, the development of a nutritional plan and some talks on health and nutrition, for a total of 7 sessions, one per week. A more detailed description of this approach can be found elsewhere (Morillo‐Sarto et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Two such approaches are mindful eating and YogaDance. Mindful eating has recently attracted much attention in nutrition research [ 6 , 7 ]. In short, mindful eating aims at aligning eating habits with inner hunger and satiety signals rather than counting calories [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%